(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. In the conditions of fierce competition on the Ukrainian market in the sphere of providing services, one of the most important conditions for survival and achievement of sustainable development of the company in the long term is the development and implementation of a client-oriented development strategy. Its implementation can provide constant strengthening of the economic power of the company, improvement of image and reputation, expansion of the client base, and at the same time increase the competitiveness of the provided services. It is safe to say that the client today is a key factor in the success of the organization. In today’s economic environment, social responsibility is one of the most effective components of developing a customer-centric strategy for company development. Therefore, today it is relevant to implement this strategy on the basis of social responsibility. We are all users of different services and we can confidently say who we will prefer when choosing a service provider, namely: who will be responsible for their actions, behavior, decisions; to those who are transparent in the market; to who will solve your problem if necessary; ethical behavior; to one who acts according to the rules of laws and standards; to those who care about customer reliability, safety and health. The purpose of the article is to formulate the goals and actions of the client-oriented approach, to develop the client-oriented strategy on the principles of social responsibility. Results. The article identifies and analyzes the evolutionary stages development of client-oriented approach and approaches to interpretation of the concept, the author offered his vision for definition. A client-centered approach to classifying strategies by stage of economic development was proposed, and an author-based client-centered strategy was formed. Conclusiоns. Creating a client-oriented development strategy is a rather long step, which requires focusing on the main value of the company - clients, without whom it is impossible to achieve sustainable development, to get leading positions in the market of services in the conditions of turbulent state of the economic system.